2020
DOI: 10.1136/bmj.m4022
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of the Edinburgh Postnatal Depression Scale (EPDS) for screening to detect major depression among pregnant and postpartum women: systematic review and meta-analysis of individual participant data

Abstract: Objective To evaluate the Edinburgh Postnatal Depression Scale (EPDS) for screening to detect major depression in pregnant and postpartum women. Design Individual participant data meta-analysis. Data sources Medline, Medline In-Process and Other Non-Indexed Citations, PsycINFO, and Web of Science (from inception to 3 October 2018). Eligibility criteria for selecting studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
361
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 445 publications
(429 citation statements)
references
References 38 publications
6
361
0
6
Order By: Relevance
“…Concerningly, compared to historical levels of prenatal depression, the discrepancy in depressive symptoms during COVID-19 that we observed in pregnant women is even greater than has been found when comparing general population samples during COVID-19 to prepandemic samples. In the full sample of 725 pregnant women that we surveyed in March-May 2020, over 40% reported symptoms indicating possible depression when using a cutoff score of ≥ 11 on the EPDS (Levis et al, 2020). In comparison, a systematic review of studies including over 35,000 women conducted in developed countries prior to the pandemic found that the average rate of prenatal depression was 17% (Underwood, Waldie, D'Souza, Peterson, & Morton, 2016).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Concerningly, compared to historical levels of prenatal depression, the discrepancy in depressive symptoms during COVID-19 that we observed in pregnant women is even greater than has been found when comparing general population samples during COVID-19 to prepandemic samples. In the full sample of 725 pregnant women that we surveyed in March-May 2020, over 40% reported symptoms indicating possible depression when using a cutoff score of ≥ 11 on the EPDS (Levis et al, 2020). In comparison, a systematic review of studies including over 35,000 women conducted in developed countries prior to the pandemic found that the average rate of prenatal depression was 17% (Underwood, Waldie, D'Souza, Peterson, & Morton, 2016).…”
Section: Discussionmentioning
confidence: 94%
“…Whereas participants in the pre-pandemic cohort completed a modified version of the EPDS in which they were asked to report on their symptoms "during pregnancy," participants in the COVID-19 cohort were asked to report on their symptoms in the "past 7 days." According to a recent meta-analysis, the EPDS has high sensitivity and specificity for detecting depression in pregnant women at a cut-off score of ≥ 11 (Levis, Negeri, Sun, Benedetti, & Thombs, 2020). Internal consistency of the EPDS quantified with Cronbach's ⍺ was good in both cohorts (pre-pandemic cohort=.89, COVID-19 cohort=.85).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The depression level is the sum score of all the items, and higher scores indicate greater symptom severity. A threshold of 13 or more will be used to identify clinically significant symptoms [ 37 ]. Although a number of cut-off points have been used in different populations [ 38 ], maximum accuracy with a probable diagnosis of depressive disorder has been shown at this cut-off point in reviews of international EPDS validation studies [ 36 39 ].…”
Section: Methodsmentioning
confidence: 99%
“…Second, for each candidate short form, an optimal cutoff score was selected using Youden's J statistic (sensitivity + specificity −1). 50,51 The bivariate random-effects model was fit using the lme4 package. 52 Third, two non-inferiority tests were conducted for each of the 9 candidate forms to compare sensitivity and specificity, separately, to the full-length form.…”
Section: Selection Of Final Short Formmentioning
confidence: 99%